TLR-2 and TLR-4 expression in monocytes of newborns with late-onset sepsis, - Ana C.C. Redondo; Maria E.J.R. Ceccon; Ana L. Silveira-Lessa; Camila Quinello; Patrícia Palmeira; Werther B. Carvalho; Magda Carneiro-Sampaio (Jornal de Pediatria, 2014)
Objective:To analyze toll-like receptor (TLR)-2 and TLR-4 expression in monocytes of newborns with late-onset sepsis.Methods:This prospective study included 27 full-term newborns aged 8 to 29 days, with clinical and laboratory diagnosis of late-onset sepsis. Ten newborns (37%) had positive cultures. Cytokines were measured by cytometric bead array in peripheral blood, while TLR-2, TLR-4 expression, and median fluorescence intensity (MFI) were determined by immunophenotyping peripheral whole blood monocytes, and were analyzed with a BD FACSDiva flow cytometer (Becton, Dickinson and Company, USA). A comparison was performed with healthy adults.Results:Microorganisms were identified in 37% of these septic newborns, and all of them had high levels of pro-inflammatory cytokines (IL-8, IL-6, IL-1β) and anti-inflammatory cytokine (IL-10) corroborating the inflammatory/septic process. In monocytes, the frequency of TLR-4 expression was higher in infected newborns (p = 0.01).Conclusion:This study investigated the innate immune response in septic newborns. Septic newborns that relied almost exclusively on the innate immune system showed little in vivo response at monocyte activation, suggesting impaired immune response and increased susceptibility to infection.